Efficacy of treatments with toltrazuril 7.5% and lasalocid sodium in sheep naturally infected with Eimeria spp. - Rodrigues,Fernando de Souza (2016)
Abstract The objective of this study was to evaluate the efficacy of an experimental formulation of toltrazuril 7.5% + Trimix™ on a naturally acquired infection of Eimeria spp. in suckling lambs kept on pasture and, in another trial, evaluate the comparative efficacy between lasalocid and toltrazuril 7.5% + Trimix™ in newly weaned sheep under feedlot conditions that had been naturally infected with Eimeria spp. In the first experiment, 30 suckling lambs were divided into two groups: A - treated with toltrazuril 7.5% + Trimix™ and B- control. In experiment 2, 30 weaned sheep were divided into three groups: I - treated with toltrazuril 7.5% + Trimix™, II - treated with lasalocid and III - control. Treatment group A showed an efficacy of 90, 99.4 and 87.3% on days 5, 10 and 20, respectively. Treatment group I had an efficacy of 98.2, 92.6 and 94.5%, while group II had an efficacy of 72.7, 81.6 and 95.9% on days 7, 21 and 42, respectively. Eight Eimeria species were identified; E. ovinoidalis was the most common. Treatment with the toltrazuril 7.5% +Trimix ™ formulation was effective against Eimeria spp. in suckling lambs in field conditions and lambs weaned in under feedlot conditions.